Pressão do tempo e dissonância cognitiva: o efeito moderador do comportamento altruísta nas decisões de consumo - Mauer, Jocimara de Lima (Universidade do Vale do Rio dos Sinos, 2017)
Previous research has shown that in the decision-making process, consumers are often pressured by time. Furthermore, research has shown that after decision making, cognitive dissonance can occur because of the rejection of one or more attractive options. This research extends these findings and proposes that altruistic behavior influences (moderately) positively the relationship between time pressure and cognitive dissonance in consumption decisions. The one study indicate that the greater the time pressure in the decision-making process, the greater the cognitive dissonance. Study Two demonstrates that in scenarios without time pressure the consumers present greater altruistic behavior and less cognitive dissonance after the decision making. Finally, the relation between time pressure and cognitive dissonance is moderated by the low altruistic behavior when one considers the usefulness of the product. While, high altruistic behavior moderates the relation between time pressure and cognitive dissonance, considering the relevance of the decision-making.
Keywords: Comportamento do consumidor; Pressão do tempo; Dissonância cognitiva; Altruísmo; Eye tracking; Consumer behavior; Time pressure; Cognitive dissonance; Altruism; Eye tracking; ACCNPQ::Ciências Sociais Aplicadas::Administração